The Employee’s Work Life Balance on Career and Life Satisfaction: A Systematic Literature Review - Mharchelya, Mharchelya; Afdal, Afdal; Hariko, Rezki (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
This systematic literature review tries to answer the question of what methods are used to analyze how work-life balance plays a role in employee career and life satisfaction. One of the literature study approaches is Systematic Literature Review (SLR). This research uses the Systematic Literature Review with the Prism Method with the help of Watse Uake. This research is limited by only looking for Scopus Q1, Q2, Q3, and Q4 journal articles, published in 2020-2024. Based on (13) thirteen articles reviewed, through a systematic literature review process, with a time span of article publication between 2020 and 2024. It was found that only ten articles met the criteria and were used as references in this study. The results of this literature review show that by implementing work-life balance in a company, employees or workers will achieve career and life satisfaction at work